Agricultural cooperatives and the role of organisational models in new intelligent traceability systems and big data analysis - Giagnocavo, Cynthia; Bienvenido, Fernando; Ming, Li; Yurong, Zhao; Sanchez-Molina, Jorge Antonio; Xinting, Yang (International Journal of Agricultural and Biological Engineering, 2017)
Traceability systems are key to assuring food safety, creating a benefit for food supply chain components. Currently, the appearance of new technologies such as IoT and Big Data Analysis leads to a new generation of more functional, but complex, traceability systems. Organisational models based on cooperation of multiple small/medium size agents, for example of small/family farming cooperatives, play an important role in high standard agricultural production and commercialization processes. These function as both social and economic networks, with high social and economic impact in the rural areas. The case of Almeria as an example of this model was used to analyze its cooperative model. The actual traceability systems in the Almeria model were studied, taking account of the different networked agents and their interrelation. This study includes two main parts: a) analysis of the net-chains that constitute the food supply chains and their different relationships, and b) actual traceability. The next step studied how the net-chain model, including many diverse agents, may be applied to develop a new generation of traceability systems based of IoT and Big Data. This implies extending the special and functional scope of the actual systems and defining clear rules of exchange of the results of the Big Data Analysis, taking account of the adequate Privacy Rules. This work analyses the current organisation as a base for a new generation of traceability systems considered in the European project IoF2020 (Internet of the Food and Farm 2020). Some parallels between Almeria’s model and certain areas in China, mainly in the areas of Beijing-Tianjin-Hebei and Shandong were detected. Another of the objectives of this work is to deepen the understanding of these similarities and analyze the possible adaptation of the results from Almeria to China.Keywords: food traceability system, big data, internet of things, organisational structure, business model, agricultural cooperatives, net-chains, food supply chainDOI: 10.25165/j.ijabe.20171005.3089Citation: Giagnocavo C, Bienvenido F, Li M, Zhao Y R, Sanchez-Molina J A, Yang X T. Agricultural cooperatives and the role of organisational models in new intelligent traceability systems and big data analysis. Int J Agric & Biol Eng, 2017; 10(5): 115–125.